THE IMPORTANCE OF MINERAL ELEMENTS IN PLANT GROWTH AND DEVELOPMENT - Hojarxon Hikmatillayevna Mahmudaliyeva; Mastura Maxpiraliyevna Maqsudova (Modern American Journals, 2025)
This article highlights the role of mineral elements in the processes of plant growth and development. The main focus is on macro and microelements essential for plants, their physiological functions, and the conditions arising from their deficiency or excess. The article analyzes the importance of key elements such as nitrogen, phosphorus, and potassium in metabolism, cellular structure, and energy production. Additionally, it provides information about the mechanisms of mineral nutrient uptake from the soil and methods for regulating this process through agro-technical practices. This article is intended for professionals and students engaged in agriculture, biology, and ecology.
Keywords: Plant growth, development, mineral elements, macroelements, microelements, nutrition, soil fertility, physiological functions, agrotechnics, element deficiency.